Brief report on the experience of using proxy consent for incapacitated adults. Issue 1 (22nd December 2005) - Mason, S; Barrow, H; Phillips, A; Eddison, G; Nelson, A; Cullum, N; Nixon, J
Abstract : The Medicines for Human Use (Clinical Trials) Regulations 2004, which came into force in the UK in May 2004, cover the conduct of clinical trials on medicinal products. They allow a legal representative (a person not connected with the conduct of the trial) to consent to the participation of incompetent adults in medical research. Currently, very little is known about how such representatives will make their decisions. We have experience with proxy consent for older adults in a large, national trial. From 2445 potentially eligible but incapacitated patients, proxy, relative assent resulted in trial participation of only 87 (3.6%) patients. The reasons for this were that a large number of incapacitated patients had no relative available for assent (2286), but also a high proportion of relatives approached refused to provide assent (72/159, 45.3%). In comparison, 17.7% of patients declined participation in the trial. Proxy consent allowed only a small increase in trial recruitment of incapacitated patients. The fact that a greater proportion of relatives than patients refused to provide assent implies that they were more cautious than the patients themselves, or perhaps used different criteria, when making their decision. In future research involving incapacitated older patients there is likely to be heavy reliance on proxy consent provision by legal representatives. Our findings imply that consent decisions of legal representatives will not necessarily reflect those of patients themselves.